2014
DOI: 10.1176/appi.ajp.2013.13101373
|View full text |Cite
|
Sign up to set email alerts
|

Coaching in Healthy Dietary Practices in At-Risk Older Adults: A Case of Indicated Depression Prevention

Abstract: Prevention of major depressive disorder is important because current treatments are only partially adequate in reducing symptom burden and promoting health-related quality of life. Lifestyle interventions may be a desirable prevention strategy for reasons of patient preference, particularly among older patients from minority groups. Using evidence from a randomized depression prevention trial for older adults, the authors found that coaching in healthy dietary practices was potentially effective in protecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 36 publications
4
37
0
1
Order By: Relevance
“…Although Creatine Clearance similarly decreased in both groups, depression score and cognitive outcome improved significantly more in the seven days a week group than in the 6 days a week [103]. Using evidence from a randomized depression prevention trial for older adults, it has been confirmed that coaching in healthy dietary practices are effective in the protection of episodes of major depression and in the reduction of depressive symptoms to an extent from 40% to 50% [100].…”
Section: Prospective Controlled Randomized Studies On Diet and Depresmentioning
confidence: 95%
See 1 more Smart Citation
“…Although Creatine Clearance similarly decreased in both groups, depression score and cognitive outcome improved significantly more in the seven days a week group than in the 6 days a week [103]. Using evidence from a randomized depression prevention trial for older adults, it has been confirmed that coaching in healthy dietary practices are effective in the protection of episodes of major depression and in the reduction of depressive symptoms to an extent from 40% to 50% [100].…”
Section: Prospective Controlled Randomized Studies On Diet and Depresmentioning
confidence: 95%
“…Higher consumption of lactose, fiber, nonjuice fruit, and vegetables was significantly associated with lower odds of incident depression [99]. In elderly subjects a dietary coaching might be effectfull and result in a decrease in depressive symptoms and an enhanced well-being over 2 years and even less hospital admissions [100,101]. In a further randomized controlled trial, the mediterranean diet combined with nuts reduced the risk for depression [92].…”
Section: Prospective Controlled Randomized Studies On Diet and Depresmentioning
confidence: 99%
“…3 Emerging research suggests that PST is also an effective prevention strategy to reduce the incidence of major and subsyndromal depression among older adults at high risk for converting to the full clinical disorder. [8][9][10][11][12][13] The goal of PST is to help participants identify and solve problems that are contributing to stress and reduced quality of life. Components of PST include psychoeducation, active problem solving in sessions, and homework assignments where patients can apply problemsolving skills.…”
Section: Introductionmentioning
confidence: 99%
“…Because of these limitations, some nonpharmacological alternatives have been implemented, including interventions in lifestyle, behavior modification, counseling and psychological therapies (13,14). One of these therapies is meditation, which is currently being integrated into the clinical practice for some medical conditions, such as hypertension, cancer, chronic pain, diabetes, etc.…”
Section: Introductionmentioning
confidence: 99%